Angiotensin Receptor-Neprilysin Inhibitors in Patients With Heart Failure With Reduced Ejection Fraction and Advanced Chronic Kidney Disease: A Retrospective Multi-Institutional Study - Hsiao, Fu-Chih; Lin, Chia-Pin; Yu, Chun-Chen; Tung, Ying-Chang; Chu, Pao-Hsien (Frontiers in Cardiovascular Medicine, 2022)
Background Data regarding using angiotensin receptor-neprilysin inhibitor (ARNI) in patients with both heart failure with reduced ejection fraction (HFrEF) and advanced chronic kidney disease (CKD) are limited. Methods and Results Between January 2016 and December 2018, patients with HFrEF and advanced CKD (estimated glomerular filtration rate [eGFR] ≤ 30 mL/min/1.73 m2) were identified from a multi-institutional database in Taiwan. Patients who had never been prescribed with an ARNI, angiotensin-converting enzyme inhibitor (ACEI), or angiotensin receptor blocker (ARB) were excluded. We used inverse probability of treatment weighting (IPTW) to balance baseline covariates, and compared outcomes between ARNI and ACEI/ARB users. There were 206 patients in the ARNI group and 833 patients in the ACEI/ARB group. After IPTW adjustment, the mean ages (65.1 vs. 66.6 years), male patients (68.3 vs. 67.9%), left ventricular ejection fraction (30.5 vs.31.2%), eGFR (20.9 vs. 20.3 mL/min/1.73 m2) were comparable in the ARNI and ACEI/ARB groups. Over 85% of the patients had beta-blockers prescriptions in both groups (86.2 vs. 85.5%). After IPTW adjustment, the mean follow-up durations were 7.3 months and 6.6 months in the ARNI and ACEI/ARB groups, respectively. ARNI and ACEI/ARB users had a comparable risk of the composite clinical event (all-cause mortality or heart failure hospitalization) (hazard ratio [HR], 1.31; 95% confidence interval (CI) 0.91–1.88) and progression to dialysis (HR 1.04; 95% CI 0.54–2.03). In subgroup analysis, dialysis patients who used ARNIs were associated with higher incidence of heart failure hospitalization (subdistribution HR, 1.97; 95% CI 1.36–2.85). Conclusions Compared with ACEIs or ARBs, ARNIs were associated with comparable clinical and renal outcomes in patients with HFrEF and advanced CKD (eGFR ≤ 30 mL/min/1.73 m2). In short-term, HF hospitalization may occur more frequently among ARNI users, especially in patients on dialysis.